Pegada hídrica da banana nas principais regiões produtoras do Ceará - Oliveira, Vandemberk Rocha de (2018)
Water resources will be sufficient to produce the required food by 2050, though many regions will face substantial water shortages. Countries with regions with water scarcity need to plan management strategies that ensure food security for the population. The use of innovative and more efficient water resource management mechanisms will be necessary to ensure efficient allocation and use of water, guarantee access to water for domestic use and agricultural production, and to protect basic natural resources. Banana is one of the most consumed fruits in the world. World banana production reached 113.9 million tonnes. It is important to highlight that banana farming is of great importance in Brazilian agribusiness, with the Northeast contributing the highest production, approximately 32% of the national production. The research aims to determine the water footprint of the banana crop in the irrigated perimeters Jaguaribe Apodi and Tabuleiros de Russas, as well as a production area in the municipality of Missão Velha, following the methodology described by the Water Footprint Assessment Manual, which is composed of four phases: goal setting and scope; water footprint accounting; sustainability analysis of the water footprint and formulation of strategic responses. The evaluation of the water footprint can contribute to the decision-making of government and producers regarding the real value of raw water, thus raising the discussions related to the collection of raw water in the agricultural sector, implantation and crop management in the different river basins. The agricultural water footprint averages for Jaguaribe Apodi, Tabuleiros de Russas and Missão Velha were 998.3; 1,048 and 1,107 m³ t-1, respectively. For Old Mission because of the climatic conditions that require less evapotranspiration of blue water, results were obtained for blue water of 780.9 m³ t-1. For Jaguaribe Apodi and Russas these values were respectively 830.6 and 862.7 m³ t-1. The region of Missão Velha, because it presents a blue water footprint of up to 47% to the blue water footprint of the Apodi and Russas Plateau regions, indicates a region with potential to attract the irrigated crop of this crop, notwithstanding the dependence of the water source underground. The total water footprint for banana plantations in the regions of Limoeiro do Norte, Russas and Missão Velha were superior to the global water footprint in 26%, 33% and 40%, respectively